2007
DOI: 10.1002/sita.200700141
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptor and integrin signaling in phagocytes

Abstract: Specific receptors for antibodies, named Fc receptors, and for extracellular matrix proteins, named integrins, contribute to phagocyte activation. Because phagocyte activation is the mechanism whereby most of the potential pathogens are ultimately destroyed, there is a lot of interest to elucidate the biochemical signals that Fc receptors and integrins induce to activate phagocyte functions. This review describes the main signal transduction pathways that are initiated by Fc receptors and integrins in phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 140 publications
(171 reference statements)
0
42
0
Order By: Relevance
“…Then, the membrane surrounds the target particle and within few minutes it closes at the distal end, leaving a new phagosome. The signaling cascades are known in great detail for the Fc receptors and the complement receptors, since these are the best-studied phagocytic receptors [38, 67, 68]. Signaling for other phagocytic receptors is just beginning to be explored.…”
Section: Particle Internalizationmentioning
confidence: 99%
“…Then, the membrane surrounds the target particle and within few minutes it closes at the distal end, leaving a new phagosome. The signaling cascades are known in great detail for the Fc receptors and the complement receptors, since these are the best-studied phagocytic receptors [38, 67, 68]. Signaling for other phagocytic receptors is just beginning to be explored.…”
Section: Particle Internalizationmentioning
confidence: 99%
“…1C). Taken together, these results suggested that Fc␥RIIIB leads to Elk-1 activation in the nucleus via a signaling pathway that is independent of most molecules reported to participate in Fc␥R signaling (31).…”
Section: Fc␥riiib Induces Nuclear Factor Elk-1 Activation In Neutrophilsmentioning
confidence: 59%
“…Fc␥RIIA contains a cytoplasmic tail with a well-defined ITAM sequence (43). Upon cross-linking, this receptor initiates a signaling pathway that involves activation of Syk, PI3K, and also ERK (31). All of these molecules are also important for phagocytosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…FcγRIIIB, but not FcγRIIA, promoted a robust increase in phosphorylated ERK in the nucleus, and also efficient phosphorylation of the nuclear factor Elk-1 [79]. Interestingly, the FcγRIIA signaling pathway resembles the classical ITAM-mediated pathway (Figure 2) [5], while FcγRIIIB signaling pathway remains a mystery (Figure 8). Taken together, these reports strongly support the hypothesis that each FcγR is capable of initiating particular signaling pathways that lead to unique cell responses.…”
Section: Each Fcγr Initiates Particular Signaling Pathways That Lead mentioning
confidence: 98%
“…These antibodies present low affinity for microbial antigens, but they can easily activate the classical complement pathway. Complement deposited on microorganisms can induce phagocytosis via complement receptors [5,6], or it can induce bacterial lysis via the formation of the membrane attack complex [7]. At later times of the adaptive response, antibodies belong mainly to the IgG class.…”
Section: Introductionmentioning
confidence: 99%